Informal settlement segmentation using VHR RGB and height information from UAV imagery: a case study of Nepal - Sigdel, Ganesh Prasad (2021)
Dissertation submitted in partial fulfilment of the requirements for the Degree of Master of Science in Geospatial Technologies